Pott's Puffy Tumor: A Rare Manifestation - Acharya, Abhijit; Mahapatra, A. K.; Deo, Rama Chandra; Panigrahi, Souvagya (Indian Journal of Neurosurgery, 2025)
Pott's puffy tumor is a rare condition related to frontal sinus osteomyelitis and scalp abscess observed in children and young adult. Incidence of the condition in immune-competent individuals is rare. An adolescent febrile male presented with scalp swelling with nasal stuffiness and left periorbital swelling. Computed tomography (CT) brain showed frontal sinus abscess with a scalp abscess. Debridement and drainage of the abscesses were done in emergency. Repeat CT brain showed a new intracranial subdural collection. An immunocompetent individual with Pott's puffy tumor with subsequent development of subdural abscess in the postop period is a very unusual incidence.
Keywords: Pott's puffy; tumor; osteomyelitis; frontal sinusitis